1989
DOI: 10.1002/hep.1840100611
|View full text |Cite
|
Sign up to set email alerts
|

A Multicenter, Randomized, Double–Blind Trial of Somatostatin in the Management of Acute Hemorrhage From Esophageal Varices

Abstract: A prospective, randomized, placebo-controlled, double-blind, multicenter clinical trial of intravenous somatostatin (Stilamin; Serono Laboratories, Inc., Randolph, MA) was performed in 102 patients with actively bleeding esophageal varices from August, 1985, to November, 1986. Patients had major hemorrhage indicated by hematemesis or melena and evidence of significant blood loss. For entry, patients had to have endoscopic demonstration of active bleeding from esophageal varices or stigmata of recent hemorrhage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
48
0
4

Year Published

1999
1999
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 156 publications
(53 citation statements)
references
References 16 publications
1
48
0
4
Order By: Relevance
“…However, the rate of cases in which active bleeding was completely arrested using SMT alone was lower than that reported in previous randomized trials. 5,11,15 This could be the result of the fact that in this study, but not in previous trials, SMT infusion was started immediately after the admission of patients, several hours before diagnostic endoscopy was performed. Thus, the identification of an active hemorrhage during endoscopy could reflect, at least in some cases, the failure of SMT in the initial arrest of active bleeding that could have selected a group of patients with a higher risk of therapeutic failure than those evaluated in previous studies.…”
Section: Discussionmentioning
confidence: 83%
See 2 more Smart Citations
“…However, the rate of cases in which active bleeding was completely arrested using SMT alone was lower than that reported in previous randomized trials. 5,11,15 This could be the result of the fact that in this study, but not in previous trials, SMT infusion was started immediately after the admission of patients, several hours before diagnostic endoscopy was performed. Thus, the identification of an active hemorrhage during endoscopy could reflect, at least in some cases, the failure of SMT in the initial arrest of active bleeding that could have selected a group of patients with a higher risk of therapeutic failure than those evaluated in previous studies.…”
Section: Discussionmentioning
confidence: 83%
“…3 Somatostatin (SMT) was introduced for the treatment of acute variceal hemorrhage because of its capacity to decrease portal pressure and collateral splanchnic blood flow, without the adverse effects of vasopressin on the systemic circulation. 4 One placebo-controlled trial failed to show any beneficial effect with SMT, 5 although the high spontaneous success rate observed with placebo suggests that some inadvertent bias could occur in this study. 5 Furthermore, several randomized, controlled trials have shown that SMT is more effective than placebo, 6 and as effective as vasopressin, 7,8 vasopressin associated with nitroglycerin, 9 terlipressin, 10,11 and balloon tamponade, 12,13 with fewer side-effects in most of these studies.…”
mentioning
confidence: 72%
See 1 more Smart Citation
“…Causa uma vasoconstrição esplâncnica seletiva, provavelmente devido à inibição de peptídios vasodilatadores esplâncnicos, como o glucagon, peptídio intestinal vasoativo e substância P (8,14) . Além disso, por inibir a secreção gástrica, poderia evitar a dissolução do coágulo no local da hemostasia das varizes, que depende de um pH ácido (34,38) . Dois trabalhos clássicos da literatura comparando a eficácia da somatostatina com placebo no sangramento agudo de VGE, obtiveram resultados conflitantes; o primeiro, um estudo multicêntrico americano (38) , não mostrou efeito benéfico da somatostatina, ressalvado o fato de ter apresentado índice muito elevado de controle do sangramento no grupo placebo (83%).…”
Section: Discussionunclassified
“…Além disso, por inibir a secreção gástrica, poderia evitar a dissolução do coágulo no local da hemostasia das varizes, que depende de um pH ácido (34,38) . Dois trabalhos clássicos da literatura comparando a eficácia da somatostatina com placebo no sangramento agudo de VGE, obtiveram resultados conflitantes; o primeiro, um estudo multicêntrico americano (38) , não mostrou efeito benéfico da somatostatina, ressalvado o fato de ter apresentado índice muito elevado de controle do sangramento no grupo placebo (83%). Já o trabalho inglês, do Royal Free Hospital (11) , demonstrou que a somatostatina é significativamente mais eficaz que o placebo no controle da HDA por VGE.…”
Section: Discussionunclassified